Animal fats and vegetable oils – promising re-sources for obtaining effective corrosion in-hibitors for oil refinery equipment - Pyshyev, Serhiy; Romanchuk, Oleksandr; Topilnytskyy, Petro; Romanchuk, Viktoriya; Miroshnichenko, Denis; Rohovyi, Yurii; Omelianchuk, Hennadii; Parkhomov, Yurii (Національний технічний університет "Харківський політехнічний інститут", 2025)
The equipment of refineries and oil production facilities is subject to corrosion due to the supply of crude oils with a high content of mineralized water. The use of inhibitors is one of the most common corrosion protection methods. However, increasing requirements of environmental standards give impetus to developing new types of corrosion inhibitors from natural raw materials. The article deals with the synthesis conditions of new corrosion inhibitors (CIs) produced from distilled higher acids of beef fat (DHFAs) or vegetable oils (VO), as well as research on the protective effect of the synthesized corrosion inhibitors compared with industrial inhibitors (5 samples). The gravimetric method studied the protective effect in a solution of salts and jet fuel using a St20 steel plate. At 50 °C and a CIs content of 100 ppm, the protective effect of corrosion inhibitors based on VO and triethanolamine was 9.7-75.6%. Under similar conditions,CIs obtained from DHFAs and diaminoethyl exhibited a protective effect of 81.6-94.1 %. WhenDHFAs and diethanolamine were used to synthesize CIs, the protective effect was 93.0-95.6 %. CI synthesized at 130 °C and a DHFAs: diethanolamine ratio of 72: 28 showed a 99.2 % protectiveeffect at 50 °C and a CI content of 200 ppm, which was higher or equal to the impact of using industrial inhibitors (91.6-99.5%). The results prove the possibility of alternative use of animal fats and waste from their production as new resources for obtaining highly effective equipment corrosion inhibitors. Using alternative inexpensive raw materials (fats, vegetable oils, waste from their output) to obtain CIs will improve the economic performance of inhibitor production. In addition, at least the fatty (oil) part of organic CIs is biodegradable and will not harm the environment.
Keywords: biological resources; corrosion inhibitor; protective effect; higher fatty acids; vegetable oil